(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to examine the effect of varied underhand passing exercises. This study aimed to develop a spike accuracy training model for young volleyball athletes at Tulung Selapan Club using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The motivation for the study arose from the observation that many athletes experienced difficulties in performing accurate spikes, mainly due to the monotonous and conventional training methods commonly used. The developed product consisted of three training models with nine variations of exercises designed to improve spike accuracy, coordination, strength, and reflexes. Validation was conducted by three experts—an instructional media specialist, a motion expert, and a volleyball practitioner—using the Content Validity Ratio (CVR) and Content Validity Index (CVI). The validation results showed that the training model met the criteria for validity. A small-scale trial involving 15 athletes and a large-scale trial involving 25 athletes indicated that the training model achieved feasibility percentages above 70%, with ratings ranging from “good” to “very good.” These findings suggest that the developed spike accuracy training model is both feasible and effective, and it may serve as a valuable reference for coaches in designing structured, engaging, and measurable volleyball training programs.